A Model for Reconstruction the Management Philosophy, Practice, and Organization Structure in Technical and Vocational: The Public Authority for Applied Education and Training, Kuwait - Al-Ali, Salah (Technium Social Sciences Journal, 2022)
The success of technical and vocational education would depend on several factors among which are: the quality of management, the management adopted philosophy, the organization structure, the quality of workshops and laboratories, the competencies of academic and managerial staff, the level of interactions with related industries, health and safety codes and conducts, and the quality of high school graduates who are interested in joining technical and vocational institutions. However, the quality of management is considered the main dominate in the success or failure of technical and vocational education in producing graduates with the require knowledge, skills, and attitude that are mostly needed by industries. In other word, it is the mentality, philosophy, and practice that is being adopted by the management of technical and vocational education that would determine the quality of the outcomes which would consequently contributes in the reduction of the level of dependence on expatriates particularly in essential sectors of the Kuwaiti economy (e.g., oil, electricity and water, health sector, communications, and navigations). In this paper, a model is introduced to reconstruct the management philosophy, practice, and organization structure at the Public Authority for Applied Education and Training, PAAE&T, Kuwait. The aim is to tackle the weakness of the present management philosophy, practice, and organization structure and proposed instead an effective and efficient management philosophy, practice and organization structure that would enhance the quality of technical and vocational graduates. The outcomes of this paper would significantly contribute in creating a general awareness of the real notion and application of technical and vocational education and the requirements that would, without any doubt, allows a better and efficient utilization of human and material resources in achieving the overall country’s manpower plan.